Transmedia Narrative and Reading Comprehension: An Experience in Colombian Rural Education (Docentes 2.0 Journal, 2021)
Talking about transmedia implies being immersed in screens, books, music, social networks, cinema, video games, television, and many other possibilities, making it necessary to recognize an increasingly extensive reading panorama. This research was developed as a case study in the IED Republican de Francia-Escuela San Luis. The objective was to evaluate the impact of the Transmedia Narrative on the critical reading comprehension of fifth-grade students who are educated in rural areas with the model New School. From a qualitative approach, virtual ethnography was used to collect data by applying a didactic intervention designed from transmedia skills and five dimensions of critical reading comprehension: evident textual, intertextual relational, enunciative, evaluative, and sociocultural. Transmediating Colombian legends in various media, platforms, languages ??, and formats, the students showed as a first result the strengthening of the competencies corresponding to the narrative, content management, social management, use of media, and technology. Additionally, they evidenced progress in their critical reading comprehension by identifying differences between two or more texts (intertextual relational dimension), understanding underlying intentions to the stories (enunciative dimension), as well as recognizing some stereotypes or violent events within them (sociocultural dimension). Consequently, it is concluded that the Transmedia Narrative positively impacted the students' critical reading comprehension, expanding the reading panorama and generating multiple opportunities to express learning, thus strengthening the essential principles of the Escuela Nueva pedagogical model.
Keywords: Transmedia narrative; Reading Comprehension; Rural Education; Escuela Nueva